From Tradition to Translation: A Systematic Review on the Pharmacological Actions of Eugenol Extracted from Ocimum Plants in Oxidative Stress, Inflammation, and Diabetes Mellitus - Permatananda, Pande Ayu Naya Kasih; I Wayan Putu Sutirta Yasa; I Wayan Sumardika; Made Ratna Saraswati; I Gde Suranaya Pandit (HM Publisher, 2025)
Background: Ocimum species, commonly known as basil, have a rich history in traditional medicine for various ailments. Eugenol, a primary bioactive compound found in several Ocimum species, has garnered significant scientific attention for its potential therapeutic properties. This systematic review aimed to comprehensively evaluate the pharmacological actions of eugenol extracted from Ocimum plants in the context of oxidative stress, inflammation, and diabetes mellitus. Methods: A systematic literature search was conducted across major scientific databases for studies published between 2013 and 2024 that investigated the effects of eugenol derived from Ocimum plants on oxidative stress, inflammation, and diabetes mellitus. The search strategy included keywords such as